Atletizm Atlama Branşı Sporcularının Dikey Sıçrama Yüksekliği ile Wingate Anaerobik Güç Performansı Arasındaki İlişkinin İncelenmesi. - BALCI, Aydın; ÜSTÜNDAĞ, Burak; KABAK, Banu; AKINOĞLU, Bihter; KOCAHAN, Tuğba; HASANOĞLU, Adnan (Turkiye Klinikleri Journal of Sports Sciences, 2021)
Objective: The aim of this study is to examine the relationship between three different vertical jump heights and Wingate anaerobic power performance of track and field jumping athletes. Material and Methods: A total of 17 jumping events track and field athletes, 11 males, and 6 females (mean age: 17.74±1.27 years; mean body weight: 65.12±8.23 kg; mean height: 178.59±9.23 cm; mean body mass index: 20.41±1.98 kg/m²), were included. The vertical jump height of the research group was evaluated with the squat, counter movement, and free jump tests using the Microgate optojump device, and the anaerobic power performance was evaluated with the Wingate test using the Lode Excalibur Sport leg bicycle ergometer. Statistics of the study were made using SPSS 20.0 package program. Pearson correlation analysis was used to examine the relationship between variables. The statistical error level was set as p<0.05. Results: It was determined that there was a strong positive correlation between squat and active jump and peak power and average power values (r=0.793/0.664; p<0.001). It was determined that there was a very strong positive correlation between free jump and peak power, and a high level of a positive correlation between free jump and average power (r=0.823/0.758, p<0.001). Conclusion: As a result of our study, it was determined that there is a relationship between vertical jump height and anaerobic power performance in athletes. It was determined that as the vertical jump distance of the athletes in the branch of athletics jumps increased, the anaerobic power performance increased, and the anaerobic power performances of the athletes with good vertical jump height were determined.